Analysis of roles and position of mobile network operators in mobile payment infrastructure - Jan Markendahl; Mark Smith; Per Andersson (International Telecommunications Society (ITS), 2010)
A number of different mobile payment solutions have been presented the last decade. The phone subscription with its security mechanisms are used for user identification and payments. This is the case for SMS based payment and ticketing systems that are getting more and more popular. However, there are other ways to implement a Trusted Element (TE) , where a SIM card architecture is only one. It can be in the mobile phone, as a separate integrated circuit, as an optional customer deployed plug-in device (e.g., microSD) or be running as an application on a server existing entirely as software. In this paper we analyze what roles and responsibilities different actors have in different types of mobile payments solutions. The main focus is on the implications for the mobile operator business. It turns out that new types of intermediary actors in most cases play an important role. Sometimes mobile operators are not even involved. The emergence of new payment together with other non-SIM card based TE solutions opens up for many different market scenarios for mobile payment services.
Keywords: 330